ANALISIS HUKUM ISLAM TERHADAP PEMBENTUKAN DAERAH OTONOM BARU SEBAGAI UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Anwar Hidayat (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
Islam pays attention to the whole order of life, including in matters of state. The purpose of Islamic law in giving birth to the benefit of both the state and society is the mandate of Islamic law. The enactment of the regional autonomy system is a mandate given by the 1945 Constitution of the Second Amendment in 2000 to be implemented based on a law that was formed specifically to regulate regional government. The post-amendment 1945 Constitution lists the problems of regional government in Chapter VI, namely Article 18, Article 18A, and Article 18B. However, because it was considered no longer suitable to the development of the situation, state administration and demands for the implementation of regional autonomy, new rules were formed to replace it. This research is a normative juridical study, to find out Islam's view related to a country's regional autonomy. Keywords: Autonomous Region, Regional Expansion, Social Welfare